The Influence of Communication and Work Environment Through Public Service Quality on the Satisfaction of Social Assistance Recipients at the Tungkal Ilir District Office, West Tanjung Jabung Regency - Hidayatullah, Hidayatullah; Bukit, Pantun; Rozi Yamali, Fakhrul (DINASTI RESEARCH, 2026)
This study aims to identify and analyze the influence of communication and work environment on public service quality and the satisfaction of social assistance recipients, both directly and through public service quality as a mediating variable at the Tungkal Ilir District Office. The research objects include communication, work environment, public service quality, and the satisfaction of social assistance recipients, while the research subjects are social assistance recipients in Tungkal Ilir District. The study uses a quantitative approach with primary and secondary data. Primary data were obtained through surveys using Likert scale-based questionnaires designed according to the research variable indicators, while secondary data were obtained from journals, theses, books, and official documents from the Tungkal Ilir District Office. The analysis uses an interval scale to describe the condition of the variables and examine the influence among variables, providing a comprehensive overview of the role of communication and work environment in improving public service quality and the satisfaction of social assistance recipients. The sample was determined using a specific sampling technique according to the research criteria, and data were analyzed using Structural Equation Modeling (SEM) based on Partial Least Square (PLS). The results at the Tungkal Ilir District Office, Tanjung Jabung Barat, show that communication, work environment, public service quality, and social assistance recipient satisfaction fall into the categories of very good to very satisfied. Communication has a positive and significant effect on public service quality and recipient satisfaction, both directly and through public service quality, while the work environment only has a significant effect on recipient satisfaction through public service quality. These results emphasize that improving communication and work environment supports better public service quality, thereby increasing the satisfaction of social assistance recipients.